P09.17 High-resolution of neoantigen-specific T cell receptor activation patterns – moderate stimulation predicts sustained anti-tumor-response. (21st September 2022) - Füchsl, F; Untch, J; Kavaka, V; Jarosch, S; Vogelsang, C; de Andrade Krätzig, N; Gosmann, D; Rad, R; Busch, D; Beltran, E; Bräunlein, E; Krackhardt, A
Abstract : Background: Neoantigen-specific T cell receptors (neoTCRs) increasingly receive attention for anti-tumor immunotherapy. Arising from somatic mutations and aberrant posttranslational modifications, neoantigens promise safe, highly personalized targets for adoptive cell transfer. Single cell-sequencing technologies substantially advanced neoTCR identification in recent years, however, details about single-TCR-determinants for successful therapeutic administration remain to be understood. Materials and Methods: In this study, we combined high-resolution assessment of neoTCR-activation signatures with detailed in vitro and in vivo characterization of these TCRs. Single-cell TCR- and RNA-sequencing were performed from neoepitope-specifically stimulated, CD137 + -enriched peripheral-blood derived CD8 + T cells of a metastasized melanoma patient with previously determined reactivity against MS-validated neoantigens. Ex vivo-restimulation prior to analysis enabled the comparison of transcriptomic signatures of activated neoTCR-T cells. In a second step, these neoTCRs were employed for generation of transgenic TCR-T cells from healthy donors for detailed in vitro and in vivo fine-characterization. Results: Beyond confirmation of all previously known neoTCRs, this approach identified two additional clonotypes targeting KIF2C P13L in the patient. Transcriptomic comparison of all activated neoTCR-T cells revealed a spectrum of qualitatively distinct signatures with unexpectedly high heterogeneity even between TCRs sharing MHC-peptide specificity. Employing neoTCR-transgenic T cells, the TCR-intrinsic character of these differences could at least partly be illustrated. Compared to a stronger, burst-like activation pattern requiring strong negative counter-regulation, more moderate stimulation resulted in stable cytotoxicity and coincided with higher frequencies in the patient. In an in vivo xenograft model comparing rejection kinetics of different TCRs upon tumor rechallenge, TCR activity with moderate stimulation strength was associated with superior, sustained tumor control. Conclusions: By single cell-sequencing of specifically expanded, enriched and restimulated CD8 + T cells novel neoTCRs were identified. Together with detailed characterization of TCR-transgenic T cells, we describe a spectrum of qualitatively heterogeneous activation signatures within the neoTCR repertoire of one melanoma patient. Within this spectrum, moderate stimulation was associated with superior in vivo functionality. Altogether, our study provides a sensitive method for detection of neoTCRs and moreover profiling of their activation signatures. Those patterns provide valuable insights for engineering TCR-transgenic T cells for therapeutic application. Disclosure Information: F. Füchsl: None. J. Untch: None. V. Kavaka: None. S. Jarosch: None. C. Vogelsang: None. N. de Andrade Krätzig: None. D. Gosmann: None. R. Rad: None. D. Busch: None. E. Beltran: None. E. Bräunlein: None. A. Krackhardt: None.